Cloud computing and Development Practices at Cloudblitzs Pvt Ltd, Nagpur - Shamkuwar, Shreya Rashtrapal; Patil, Pragati (Journal of Neonatal Surgery, 2025)
Cloud computing has revolutionized the way businesses operate, offering flexibility, scalability, and cost-efficiency. The study explores the development practices employed by Cloudblitzs Pvt. Ltd., Nagpur, in leveraging cloud technologies to enhance operational efficiency and innovation. With the growing adoption of cloud solutions in various sectors, Cloudblitzs Pvt. Ltd. stands as a prominent player in implementing cutting-edge cloud computing strategies. This research investigates the company’s approach to cloud adoption, its integration with existing IT infrastructure, and the strategies employed to ensure seamless development and deployment of cloud-based applications. Additionally, it highlights the challenges faced during implementation, such as data security concerns, resource management, and the need for continuous skill upgrades among employees. By examining the company's cloud adoption lifecycle, from planning and migration to ongoing maintenance and scaling, the study provides valuable insights into the practical aspects of cloud computing. This analysis aims to provide a framework for businesses looking to adopt cloud solutions while addressing potential barriers and offering recommendations for improved implementation practices. Furthermore, the research emphasizes the importance of innovation, collaboration, and strategic planning in the successful integration of cloud computing technologies in business processes